answersLogoWhite

0

-2(3a+2)+2=

User Avatar

Wiki User

9y ago

Still curious? Ask our experts.

Chat with our AI personalities

BeauBeau
You're doing better than you think!
Chat with Beau
RafaRafa
There's no fun in playing it safe. Why not try something a little unhinged?
Chat with Rafa
CoachCoach
Success isn't just about winning—it's about vision, patience, and playing the long game.
Chat with Coach

Add your answer:

Earn +20 pts
Q: -2(3a plus 2) plus 2
Write your answer...
Submit
Still have questions?
magnify glass
imp
Continue Learning about Math & Arithmetic

Which is a distributive property - 23a 1 6a 2 or- 23a 1 - 6a 1?

Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "times", "equals".


What is 2 plus 2 plus 2 plus 2 plus 2 plus 2 plus 2 plus 2 plus 2 plus 2 plus 2 plus 2 plus 2 plus 2 plus 2 plus 2 plus 2 plus 2 plus 2 plus 2 plus 2 plus 2 plus 2 plus 2 plus 2?

16 + 20 + 14 = 50 = 12 + 14 +14 + 10


What two numbers would have a product of 108 and a sum of 23 at the same time?

Here's one way to work that out. Let's call the numbers "a" and "b" We're told: a + b = 23 ab = 108 We can take one of those two, solve it for either a or b, substitute it into the other, and solve for the other variable using our new equation: a + b = 23 b = 23 - a ∴ a(23 - a) = 108 -a2 + 23a = 108 a2 - 23a + 108 = 0 a2 - 23a + (23/2)2 = (23/2)2 - 108 (a - 23/2)2 = 529/4 - 432/4 (a - 23/2)2 = 97/4 a - 23/2 = ± √(97/4) a = (23 ± √97) / 2 So the two numbers that meet this condition are (23 - √97) / 2 and (23 + √97) / 2


What is the mean of 2 plus 2 plus 2 plus 2 plus 2 plus 2 plus 1 plus 2 plus 2 plus 2 plus 1 plus 2 plus 2 plus 2 plus 2 plus 2 plus 2?

To find the mean (or average) you first add up the numbers you have. NOTHING 1.88


What is sin23A minus sin7A upon sin2A plus sin14A if A equals pi upon 21?

Using the identity, sin(X)+sin(Y) = 2*sin[(x+y)/2]*cos[(x-y)/2] the expression becomes {2*sin[(23A-7A)/2]*cos[(23A+7A)/2]}/{2*sin[(2A+14A)/2]*cos[(2A-14A)/2]} = {2*sin(8A)*cos(15A)}/{2*sin(8A)*cos(-6A)} = cos(15A)/cos(-6A)} = cos(15A)/cos(6A)} since cos(-x) = cos(x) When A = pi/21, 15A = 15*pi/21 and 6A = 6*pi/21 = pi - 15pi/21 Therefore, cos(6A) = - cos(15A) and hence the expression = -1.